The supreme macaroni company ebook A novel. - Trigiani, Adriana (Valentine Trilogy, 2013)
New York Times Bestseller • Publishers Weekly Bestseller In The Supreme Macaroni Company, bestselling author Adriana Trigiani weaves a heartbreaking story that begins on the eve of a wedding in New York's Greenwich Village and culminates in beautiful Tuscany. Family, work, romance, and the unexpected twists of life and fate all come together in an unforgettable narrative that Trigiani fans will adore. For over a hundred years, the Angelini Shoe Company in Greenwich Village has relied on the leather produced by Vechiarelli & Son in Tuscany. This ancient business partnership provides the twist of fate for Valentine Roncalli, the schoolteacher turned shoemaker, to fall in love with Gianluca Vechiarelli, a tanner with a complex past . . . and a secret. But after the wedding celebrations are over, Valentine wakes up to the hard reality of juggling the demands of a new business and the needs of her new family. Confronted with painful choices, Valentine remembers the wise words that inspired her in the early days of her beloved Angelini Shoe Company: "A person who can build a pair of shoes can do just about anything." Now the proud, passionate Valentine is going to fight for everything she wants and savor all she deserves—the bitter and the sweet of life itself.